THE DYNAMICS OF SOCIAL AND POLITICAL RELATIONS IN THE CONTEXT OF DEMOCRATIC TRANSFORMATION IN TURKEY - Hasan Çelik; İbrahim Şahin; Ali Öztürk; Emre Aydın (International Journal of Education and Social Science Studies, 2025)
This study examines the evolving dynamics of social and political relations in Turkey amid its ongoing democratic transformation, focusing on how diverse social forces interact with the state and shape the trajectory of democratization. Positioned between Europe and Asia, Turkey provides a complex setting where formal democratic institutions coexist with increasing authoritarian tendencies.  Employing a qualitative, descriptive-analytical approach, the research analyzes developments from the early 2000s to the post-2016 period, drawing on policy documents, political speeches, academic literature, and civil society reports. It explores how state authority engages not only with organized civil society but also with broader social actors—such as media networks, religious communities, gender-based movements, and digital activism—that influence political participation and public discourse. The findings indicate that while constitutional and institutional reforms have expanded the procedural framework of democracy, substantive aspects—particularly freedom of expression, media independence, and pluralism—remain constrained by centralizing state power. Nevertheless, new forms of civic engagement, including online mobilization and gender equality campaigns, demonstrate society’s adaptive strategies and resilience. Democratization in Turkey thus emerges as a non-linear and contested process, shaped by the tension between state control and the plural aspirations of its citizens. By integrating social dimensions and empirical illustrations, this study offers a nuanced contribution to understanding how hybrid regimes negotiate power, participation, and identity in transitional democratic contexts,